EFEK MODERASI STATUS SEKOLAH TERHADAP PENGARUH SARANA PRASARANA, KOMPETENSI, DAN PROFESIONALISME TERHADAP SIKAP KERJA KEPALA SMP DI KABUPATEN SUKOHARJO - Sarno Sarno (JURNAL ILMIAH EDUNOMIKA, 2021)
The research is aimed to analyze the moderating effect of school status on the effect of school facilities, principals’ competence, and principals’ professionalism on job attitudes among Junior High School Principals in Sukoharjo. It employs a survey method using census model with the population of 78 principals of Junior High School Principals in Sukoharjo. The data collection technique is done using questionnaires. The data is analyzed using hierarchical multiple regression analysis. Based on the analysis, the research concludes that: (1) the school facilities, principals’ competence, and principals’ professionalism have significant effect on job attitudes both partially and simultaneously; (2) the school status moderate the effect of the school facilities and principals’ professionalism on job attitudes Keywords: Job attitudes; school facilities; competence; professionalism.